agglomerates
Patent Information
- Application Number
- CN202180063882.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-21
- Filing Date
- 2021-09-20
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2041-09-20
Smart Images

Figure BDA0004130923280000091 
Figure BDA0004130923280000101 
Figure BDA0004130923280000121
Abstract
Description
[0001] This invention relates to the use of fibers in agglomerates, and to the production of agglomerates, for example, from coal, metals, or metal ores. Typically, agglomerates are formed from particulate materials and fibers.
[0002] A vast quantity of powdered minerals exists worldwide. These typically originate as waste from industries such as mining, manufacturing, and power generation; and if further processed, they represent a significant potential resource for energy or metal production. However, it is difficult to process such powders into a stable form that can be transported not only to the point of use but also within the large processing plants at their destination. This problem is exacerbated when the granules are produced using wet processes or stored under humid conditions, resulting in high moisture content.
[0003] Adding fibers to reinforce industrial systems is known; for example, it has been known for many years to add polypropylene fibers to concrete to strengthen the concrete matrix while reducing shrinkage and cracking.
[0004] It is advantageous to provide granulation / briquetting methods in which the briquettes exhibit improved stability, particularly when the granular matrix is wet. This can provide, for example, the processing of these metal ore briquettes from concentrated fine powders with high moisture content using extrusion technology, as well as the briquetting of fine metal powders using liquid binders, where the density of the powders limits the amount of liquid that can be added.
[0005] The present invention aims to overcome or improve at least some aspects of these problems.
[0006] Therefore, in a first aspect of the invention, clumps are provided comprising particulate material; and fibers, typically ranging from 0.1% to 0.5% by weight of the clumps. It has been found that adding fibers to the particulate material alters the rheology of the clumps and stabilizes the moisture content. This allows the particles to be processed into clumps of acceptable strength (green pellet strength and cured strength), enabling them to be transported and stored without excessive degradation, even if the particulate material is not dried. The ability to omit the drying step saves significant time and energy costs and eliminates the risk of chemically altering the particles during the drying process. Furthermore, it has been found that the presence of fibers increases the porosity of the pellets, thereby increasing the surface area of the particulate material in contact with air. This can be advantageous when the pellets contain materials that will undergo chemical reactions, as the porosity provides improved penetration of reagents into the material. One example of this could be the reduction of iron ore in a blast furnace. Another example could be coating the binder surface with a wetting agent, which can be done more effectively in cases where large pore volumes exist within the clumps. In the case of granular materials that are metal ores, another advantage is that the fibers alter the rheology of the material, thereby improving the granules’ resistance to shear and facilitating briquetting via roll briquetting technology.
[0007] As used herein, the term "fiber" is intended to refer to any thread or filament of composition. It typically refers to a fiber having a length ranging from 15 μm to 5 mm or from 15 μm to 3 mm (typically 50 μm to 2 mm, or 0.1 mm to 1 mm), and a diameter ranging from 10 μm to 100 μm (typically 15 μm to 50 μm). Optionally, the fiber length ranges from about 0.2 mm to about 5 mm, typically from about 0.3 mm to 4 mm. Fiber diameter: The length-to-length ratio makes the fiber longer than its width. It has been found that, generally, the longer the fiber, the greater its stabilizing effect, because the fiber's adhesion to particulate materials increases with length through changes in rheology that complicate the process.
[0008] In practice, fibers are typically provided with a "D90" value, which means that 90% of the fibers have a length within this range. The D90 value of the fibers used in this invention is typically at least 0.2 mm, preferably 0.2 mm to 5 mm.
[0009] Fibers can be natural or synthetic, unused or recycled, and can be selected from synthetic polymers, natural polymers, and combinations thereof. Synthetic polymers can be selected from polypropylene, polyethylene, polyester, polyacrylonitrile, polyamide, or mixtures thereof. For example, if the synthetic polymer is derived from recycled textiles, a mixture can be formed. Natural polymers can include plant (including wood) fibers and animal fibers; generally, natural polymers will be absorbent, but this is not necessary. For example, wool can be used, as can cellulosic fibers such as cotton, jute, flax, hemp, and sisal. In addition, wood fibers derived directly from wood pulp or from the paper industry can be used. As used herein, the term "paper" is intended to be a comprehensive term for both paper and cards. Cellulosic fibers can be composites with synthetic polymers or other natural polymers. Typically, the fiber will be a cellulosic fiber, usually recycled for environmental reasons. As used herein, in contrast to composites, references to "fiber" will refer to fibers containing a major fibrous component (e.g., cellulose) in the range of 80% to 100% by weight (typically 90% to 100% by weight).
[0010] Typically, fibers are present in the range of 0.1 wt% to 0.5 wt% of the aggregates, usually in the range of 0.1 wt% to 0.4 wt%, or 0.2 wt% to 0.3 wt%. At these levels, fibers alter the rheology of the aggregate material, thereby allowing for processing and reinforcement without introducing excessively high levels of porosity that would cause the strength to begin to decrease relative to particles without fibers.
[0011] The fibers can be in fibrous, granular, or powder form, but are typically in granular form. The granules can have a particle size distribution such that 60% to 90% of the granules will pass through a 5.6 mm sieve (US 3.5 mesh), typically 60% to 90% of the granules will pass through a 4.75 mm sieve (US 4 mesh), or 60% to 90% of the granules will pass through a 4.5 mm sieve.
[0012] The bulk density of fibers can range from 10 g / l to 1500 g / l, typically from 20 g / l to 500 g / l, or from 200 g / l to 300 g / l. At these densities, fibers can be added to particulate materials without significant loss of agglomerate density or potential synthetic loss of agglomerate strength.
[0013] This typically involves the following: the fibers are insoluble in water and generally have a low moisture content. Using insoluble fibers prevents their dissolution under clump storage conditions, ensuring no loss of strength. Maintaining a low moisture content ensures that adding fibers to granular materials (which are typically wet, making processing granules difficult without fibers) does not further increase the moisture content of the clump mixture, potentially exacerbating the aforementioned problems surrounding the processing of wet granules.
[0014] Yes, cellulose fibers include CFF Topcel. TM CFF Topcel is a granular recycled paper product containing more than 80% cellulose, with a bulk density ranging from 200 g / L to 280 g / L, a moisture content ≤7% by weight, and a particle size distribution such that 60% to 90% of the particles will pass through a 4.5 mm sieve. Cellulose fibers can also be produced from CreaFill. TM Provided by USA.
[0015] The particulate material can be selected from metal ores, metal ore-containing waste, iron slag, iron filings, mineral waste, carbon-containing materials, electric arc furnace waste, or a combination thereof.
[0016] Metal ores typically include iron ore. Iron ore can be any naturally occurring or non-natural ore, such as hematite, magnetite, or chalcedony, and may contain naturally occurring contaminants.
[0017] When the particulate material is carbonaceous, it can be coke, graphite, carbon black, peat, or coal. Typically, the particulate material will contain coke and / or coal. As used herein, the term "coal" is intended to include lignite, sub-bituminous coal, bituminous coal, steam coal, and anthracite. Coke has been found to be particularly problematic in forming brittle brittle, and therefore the present invention provides a particular benefit in providing more robust coke brittle.
[0018] Mineral waste includes steel scrap, steel sludge, and fine powder from ore or metal-containing waste.
[0019] The metal can be, or the metal ore or mineral waste can contain: iron, zinc, nickel, copper, chromium, manganese, gold, platinum, silver, titanium, tin, lead, vanadium, cadmium, beryllium, molybdenum, uranium or mixtures thereof, or elemental metals, or in the form of, for example, oxides or silicates.
[0020] Particulate iron slag typically originates from tailings ponds or washing systems and is generally ultrafine. That is, at least 90% of its particles are smaller than 200 μm, and typically at least 50% are smaller than 20 μm. Iron slag is typically iron oxide. Recycled iron and ferroalloy byproducts, which are highly spherical in form and have a narrow particle size distribution, may exhibit difficulty in agglomeration. This is due to several factors, such as low levels of mechanical interlocking, a polished matrix, high density, and low surface area. However, recycled iron and ferroalloy byproducts are more readily agglomerated when used for agglomeration as disclosed herein.
[0021] Granular material can advantageously be MDF sawdust. MDF sawdust is a product made from hardwood and softwood fibers bonded together using a urea-formaldehyde binder. One advantage is that the binder in MDF helps to bind clumps together. Formaldehyde is a potential carcinogen and can be adsorbed by dust particles, which can be toxic if inhaled or if the particles come into contact with human skin. For this reason, MDF sawdust is considered hazardous waste and difficult to dispose of. Therefore, incorporating this product into clump products is a good way to dispose of this waste and is therefore environmentally beneficial.
[0022] It should be noted that the term "lumps" includes objects commonly referred to as pellets, rods, strips, clumps, and blocks. These objects share the common characteristic of being in a compacted form of material and are primarily distinguished by their size and shape. Agglomerates can be thermoformed or cold-formed, but are typically cold-formed due to the presence of fibers. As used herein, the term "cold-formed" is intended to mean forming without applying heat before being placed in a furnace, such as without sintering, or without heating to above 60°C, above 40°C, or 30°C. Conventionally, agglomerates are formed using thermal working, thus producing so-called thermally bonded (hardened) agglomerates. Thermoformed / bonded agglomerates have their strength increased through heat treatment, resulting in a combination of ceramic properties and associated porosity. Porosity provides voids that allow for some expansion and release of internal stress. This is particularly important in the case of agglomerates from metallic ores, as the reduction of the metal (e.g., the conversion of hematite to magnetite in iron ore) leads to volume changes and stress on the agglomerate. Since this void formation does not occur during cold pellet formation, alternative methods are needed to prevent pellet disintegration under internal stress. As described in this paper, the solution is to incorporate fibers. Unbound by theory, it is argued that the presence of fibers provides space for crystal growth, which would otherwise induce microcracks in the agglomerates, reducing agglomerate strength and leading to disintegration.
[0023] Depending on the desired compaction level, the compaction level of the pellets can be varied, for example, by subjecting the mixture of granular iron ore and binder formulation to a larger or smaller vacuum. A larger vacuum level will increase the compaction of the pellets. Alternatively, this can be controlled by the amount of pressure used to form the pellets.
[0024] The lumps typically have a maximum average diameter of 20 mm, more commonly 16 mm or 15 mm; a minimum average diameter of 2 mm, particularly 5 mm; or an average diameter of 10 mm to 12 mm. These objects are characterized by being in a compacted form of material and are primarily distinguished by their size and shape.
[0025] The particulate material can be powder or shavings. Typically, the particle size is 4 mm or smaller (widest axis). Particle sizes usually range from 0.1 mm to 4 mm. Generally, at least 10% by weight of the particulate material is able to pass through a 100 μm sieve before forming agglomerates. In the case of materials with these particle sizes, agglomeration is most useful because such fine particles are difficult and hazardous to transport. Furthermore, the presence of smaller particles in the particulate material improves material packing.
[0026] The lumps may additionally contain a binder. For example, the binder may include cement. As used herein, the term cement is intended to refer to inorganic cement.
[0027] The agglomerate may also contain a binder selected from the following: at least partially saponified polyvinyl alcohol, combinations of polyvinyl alcohol and sodium hydroxide, alkali metal alkyl silicates or polyalkyl silicates, phenolic resins, guar gum (typically 5000 cps grade), combinations of guar gum and calcium oxide, anionic polyacrylamide, styrene-acrylate emulsions, polysaccharide binders, and combinations thereof. Binders from this list may be present independently or in addition to cement. These binders will be selected based on the conditions the agglomerate will experience and the properties of the particulate matter, according to the agglomerate's function.
[0028] When the binder is polyvinyl alcohol (PVA), it is typically formed from polyvinyl acetate in a process called saponification, where hydroxyl groups replace the acetate groups of the acetate ester by reacting the polyvinyl acetate with sodium hydroxide. "Partial saponification" means that some acetate groups have been replaced by hydroxyl groups, resulting in at least partially saponified PVA containing vinyl alcohol residues. Typically, the degree of saponification of PVA is at least 80%, usually at least 85%, at least 90%, at least 95%, 98%, 99%, or 100%. PVA is commercially available, for example, from KurarayEurope GmbH in Frankfurt Am Main, Germany. PVA is typically used as an aqueous solution. PVA can be modified to include sodium hydroxide content. Typically, PVA binders in solution have an active polymer content of 12% to 13% and a pH in the range of 4 to 6.
[0029] When the binder is an alkali metal alkyl silicate, it can be an alkali metal C1 to C4 alkyl silicate, such as an alkali metal methyl silicate. Alternatively, the methyl portion can be replaced by an ethyl, propyl, or butyl portion. Typically, the alkali metal is sodium or potassium, most commonly potassium. Most commonly, potassium methyl silicate, for example, sold by Wacker Chemie GmbH under the trade name Silres, is used. This has been found to produce lumps with better drop resistance. Furthermore, it surprisingly produces thermally stable lumps, which are able to essentially maintain their shape in a reducing atmosphere up to 1200°C. Alkali metal alkyl silicates are typically reacted with carbon dioxide during the curing process to produce equivalents of polyalkylsilicic acid, such as polyC1 to C4 alkylsilicic acid, like polymethylsilicic acid. They are conventionally used as waterproofing agents for masonry; however, it has been found that the strength of the lumps can be improved by adding silicates or polyalkylsilicic acids.
[0030] Phenolic resins are commonly known in the art. Typically, this resin is a formaldehyde-to-phenol ratio greater than 1, usually about 1.5, that of a primary phenolic resin or phenolic varnish resin. The resin can be used as a powder or as an aqueous solution mixed into particulate matter.
[0031] Guar gum can be added with acrylamide at a ratio of 4 to 12 parts by weight, most commonly 5 to 10 parts or 8 parts polyacrylamide to 1 part guar gum. Typically, 3 parts calcium oxide can be added.
[0032] It has been found that some very fine powdery waste materials or mineral powders (e.g., electric arc furnace waste) present problems when mixed with binders such as polyvinyl alcohol. The inventors have discovered that using polysaccharide binders such as starch, particularly pregelatinized potato starch, instead of or in combination with polyvinyl alcohol, can advantageously improve the production of lumps from such waste materials.
[0033] Typically, lumps will contain 0.01% to 1.5% by weight, usually 0.1% to 1.0% by weight, or 0.2% to 0.8% by weight of binder. However, in cases where the binder contains cement, there is typically 5% to 10% by weight of binder.
[0034] When the binder contains polyvinyl alcohol, the lumps may contain 0.01% to 0.8% by weight of the binder. More typically, they contain 0.5%, 0.4%, or 0.3% by weight of polyvinyl alcohol binder. When the binder contains alkali metal alkyl silicates or polyalkyl silicates, they are typically used in the range of 0.01% to 0.5% by weight, more typically 0.5% or 0.2% by weight of the material. When the binder contains phenolic resin, the lumps will typically contain 0.5% to 1.5% by weight of this resin. It has been found that phenolic resin, especially in these amounts, provides particular strength benefits when the particulate material is iron ore. Typically, when the binder is anionic polyacrylamide, it will be present in the range of 0.5% to 1.0% by weight. When the binder contains styrene-acrylate emulsion, this is typically present in the range of 0.5% to 1.5% by weight, more typically about 1% by weight. Typically, styrene-acrylate emulsion will be present in combination with cement. In this case, the cement will typically be present in the range of 5% to 10% by weight, usually 8% inorganic cement.
[0035] The polysaccharide binder can be starch, which can be pregelatinized potato starch. For example, it can be provided as up to 0.8% by weight, particularly 0.6% by weight, of the granular material by mixing 10% by weight of the binder solution with the granular material. In the case that the granular material is electric arc furnace waste, up to 0.5% by weight of polyvinyl alcohol as defined above can be added to the granules.
[0036] In cases where the particulate material contains metal ore or metal ore-containing waste, the binder will typically include phenolic resin, with optional polyvinyl alcohol and optional guar gum. Polyvinyl alcohol will typically be present in the range of 0.1% to 0.2% by weight, usually about 0.125% by weight, and guar gum may be present in the range of 0.5% to 1.05% by weight, usually about 0.5% by weight.
[0037] For example, in the case of particulate material being metallic ore, the binder may also contain carbon additives to promote the reduction reaction. The carbon additives will typically contain 80% to 100% by weight of carbon, typically 90% to 99% by weight, and will generally be selected from carbonaceous materials with low volatility that do not undergo volume changes (e.g., through expansion) within the agglomerates. Typically, the carbon additives will be selected from anthracite, semi-coke, coke, or combinations thereof. Where present, the carbon additives will typically range from 1% to 25% by weight, typically from 5% to 20% by weight.
[0038] The strength and resilience of the aggregates can be further improved by adding a suitable crosslinking agent. Suitable crosslinking agents include, for example, 0.01% to 5% by weight of glutaraldehyde. Sodium hydroxide, for example, at 0.1% by weight, can also be used as a crosslinking agent. Other crosslinking agents include glyoxal, glyoxal resins, PAAE resins (polyamide amine chlorohydrin), melamine formaldehyde, and organic titanates (e.g., DuPont's Tizor). TM The crosslinking agent is typically used at a rate of up to 5% by weight, and more commonly 3% or 2% by weight. This reduces the amount of binder (such as polyvinyl alcohol) from, for example, 0.8% or 0.5% by weight to, for example, 0.3% or 0.4% by weight. This is a cost-effective way to increase the strength of the material. Therefore, the crosslinking agent is typically present with the polyvinyl alcohol binder, which usually contains partially saponified components, such that the combination can be: 0.01% to 0.5% by weight of fully saponified polyvinyl alcohol, 0.01% to 0.5% by weight of partially saponified PVA, and 0.01% to 5% by weight of crosslinking agent. Typically, a 1:1 ratio of fully saponified polyvinyl alcohol to partially saponified polyvinyl alcohol is used. Typically, when used with polyvinyl alcohol, 0.01% to 0.04% by weight, particularly 0.02% by weight of glutaraldehyde is used as the crosslinking agent. This combination of polyvinyl alcohol binder and crosslinking agent has been found to be particularly useful in stabilizing particulate mineral waste.
[0039] Thus, it has been determined that the selection of crosslinking agents can improve the properties of clumps. Another example is a binder containing 0.01% to 5% polyvinyl alcohol and 0.01% to 0.5% by weight, particularly 0.02% by weight, sodium hydroxide. It has been found, particularly in the case of metal ores and waste such as hematite, that sodium hydroxide produces improved properties compared to, for example, glutaraldehyde. They can be used or manufactured as defined above.
[0040] The use of phenolic resin and a hardener advantageously combines coke and pulverized coal. Therefore, the lumps may also contain a hardener. The phenolic resin can be used in amounts up to 4% by weight or up to 2% by weight. The phenolic resin can typically be used either as an aqueous solution or in conjunction with a hardener. The hardener can be, for example, ethylene glycol triacetate and gums such as guar gum, gum arabic, and gum arabic. Typically, 0.1% to 0.5% by weight of ethylene glycol triacetate and 0.1% to 0.5% by weight of gum are used. This can be achieved by cold curing.
[0041] However, the agglomerates can additionally contain a waterproofing agent to further enhance water resistance; in the case of an alkali metal alkyl silicate binder, it can also function as a waterproofing agent. Where present, the waterproofing agent can be combined with the particulate material or served as a layer on the outer surface of the agglomerate.
[0042] Waterproofing agents are typically sprayed onto the outer surface of the clumps after they have formed. Common waterproofing agents include styrene-acrylate copolymers, such as Vinnapas. TM SAF 34 (Wacker Chemie AG, Munich, Germany) is typically a fine particulate dispersion of a styrene-acrylate copolymer, generally free of alkylphenol polyoxyethylene ethers, and optionally may contain 0.05% to 1% guar gum. Alternatively, lumps can be coated by spraying a layer of asphalt emulsion. Alternatives to spraying lumps with material include, for example, immersing the lumps in a solution or dispersion of the waterproofing material, or combining the waterproofing material with particulate materials and binders.
[0043] Typically, lumps contain <15% by weight, <10% by weight, or <5% by weight of water. If necessary, the moisture content can be reduced by drying, for example by adding up to 3% quicklime (calcium oxide). However, the purpose of this invention is to eliminate the need for drying particulate matter in most cases.
[0044] Processing aids may be present. These may include additives selected from polysaccharides, cellulose thickeners, and combinations thereof. Typically, polysaccharides and / or cellulose thickeners are selected from guar gum, gum arabic, xanthan gum, starch, hydroxyethyl cellulose, methyl cellulose, methyl hydroxyethyl cellulose, and combinations thereof. These processing aids have been found to both thicken and stabilize the pellets, thereby reducing chemical degradation and improving shelf life. Furthermore, the selection of non-cement-based processing aids eliminates the common problem of increased slag generation during iron processing, and the present invention is characterized by the elimination of the need for cement-based or clay-based processing aids. Guar gum and methyl hydroxyethyl cellulose are commonly used because these processing aids have been found to not only facilitate the processing of iron ore into pellets but also further improve green pellet strength compared to pellets containing only silicates. Guar gum can be used where environmental certification of iron ore pellets is important because it is a natural product. Processing aids may be present in the formulation at a range of 5% to 25% by weight or 10% to 20% by weight. It has been found that, in the case of extrusion processing, these levels of processing aids prevent extruder stalling caused by blockage or other particulate matter entering the structure of the extruder.
[0045] A setting agent may also be present, which can promote the polymerization of silicates, thereby leading to gelation and enhanced agglomeration. The setting agent can be selected from glyceryl triacetate, epoxypropoxypropyltrimethoxysilane, pyrolytic silica, potassium methylsilicate, and combinations thereof. Typically, the setting agent will contain epoxypropoxypropyltrimethoxysilane because it provides excellent adhesion. The setting agent can be present in the range of 0.5% to 1.0% by weight of the adhesive formulation.
[0046] In a second aspect of the invention, a method for producing clumps according to the first aspect of the invention is provided, comprising: mixing particulate material with fibers in the range of 0.05% by weight to 0.5% by weight; compressing the mixture to form clumps; and curing the clumps. The method may include an additional step of mixing one or more of an adhesive, a crosslinking material, and / or a waterproofing agent with the particulate material.
[0047] Typically, mixing is accomplished using a biaxial batching mixer because continuous mixers often cannot control the amount of material precisely enough.
[0048] Compression can be achieved using molds, roller presses, or extrusion. Typically, a roller press is used to compress the mixture to form clumps. In the presence of a binder, a vacuum can be used to improve binder absorption; however, this is usually unnecessary.
[0049] The clump can then be cured, for example, for 12, 24, or 48 hours. Typically, this process is carried out at ambient temperatures, such as 0°C to 40°C, 15°C to 30°C, 20°C to 25°C, or 20°C.
[0050] Unless otherwise stated, as those skilled in the art will understand, each described integer can be used in combination with any other integer. Furthermore, while all aspects of the invention preferably “comprise” the features described with respect to that aspect, it is particularly contemplated that they may “consist” or “substantially constitute” those features outlined in the claims. Moreover, unless expressly defined herein, all terms are intended to be given in their meaning as commonly understood in the art.
[0051] Furthermore, in the discussion of this invention, unless otherwise stated, the disclosure of optional values for the upper or lower limits of the permissible range of a parameter should be interpreted as the following implied statement: each intermediate value of the parameter (between the smaller and larger alternatives) is itself disclosed as a possible value of the parameter.
[0052] Furthermore, unless otherwise stated, all numerical values appearing in this application should be understood to be modified by the term "about". The term "weight %" and similar terms are intended to refer to the weight percentage of the total aggregate composition.
[0053] To make the invention easier to understand, the invention will be further described with reference to specific embodiments described below.
[0054] Example 1: Magnetite
[0055] Magnetite samples containing 65 wt% Fe3O4 and 2 wt% to 30 wt% FeO (particle size <90 μm) were provided. They were formed into agglomerates using a HUTT-Greaves roller press (pressure 200 bar). The fibers used were CFFTopcel fibers (cellulose fibers). Moisture content and fiber levels were varied as shown in Table 1 below.
[0056] Table 1
[0057]
[0058]
[0059] #The average value of 50 ISO 4700 tests
[0060] *ISO 7215 – Expected results in the range of 60% to 80%
[0061] It can be seen that, in the absence of fibers, the dry sample provides a cured strength just below 4000 N, which is sufficient to allow transportation and storage without damage or disintegration, and processing in a blast furnace. However, the RI (Reduction Index), a measure of the reduction rate due to oxygen loss, is below the 60% threshold level for reduction rate. Failure to meet this standard negatively impacts the marketability of the product.
[0062] When the moisture content increases to 8% by weight, simulating the effects of mineral storage in a humid environment, the agglomerates become difficult to process in the absence of fibers. The formed agglomerates exhibit poor integrity and high loss levels (leading to low yields). This is evidenced by low post-solidification crushing strength and low RI (recovery ratio).
[0063] However, when 0.2 wt% fiber was added to the mineral in the presence of the same level of moisture (8 wt%), very good agglomerates were formed. These exhibited good green pellet crushing strength, allowing for processing without concern for disintegration, and solidified crushing strength comparable to that of dry minerals, as well as excellent RI values. Therefore, this test demonstrates the benefits of the presence of fiber in the following ways:
[0064] • The steady-state rheology of the mixture provides good compaction parameters
[0065] • Reinforce the structure to increase strength
[0066] • Enables materials to be processed with increased moisture content.
[0067] Furthermore, studies on agglomerate structures show that the increased porosity of agglomerates increases the total surface area on which reduction can occur (e.g., during processing to extract metal). This results in improved processing time for agglomerates.
[0068] Example 2: Iron ore pellets and fine powder
[0069] Agglomerates were formed from fine hematite powder (>65% Fe) containing 0.25 wt% cellulose fibers and an organic binder. Less degradation was observed during the reduction process of hematite to magnetite (Fe₂O₃→Fe₃O₄ at 500°C to 760°C) compared to the absence of fibers. As mentioned above, this is believed to be because the fibers provide space for crystal growth that would otherwise occur during this transformation, creating microcracks in the agglomerates, thus reducing agglomerate strength and leading to disintegration.
[0070] The test results provided in Table 2 below illustrate this principle.
[0071] No fiber 53.2 -3.15mm Fiber 18.3, 12.0 -3.15mm
[0072] *Reduced Disintegration Index (ISO) 4696-2
[0073] It is clear that fibers significantly improve the RDI value of agglomerates (by 38%). Generally, it is desirable for the RDI value of iron ore agglomerates to be as low as possible (ideally below 10).
[0074] Example 3: High-grade anthracite
[0075] Typically, anthracite must be washed to provide a clean product before it can be formed into briquettes. This results in a wet product (ultrafine tailings in water) that must be dehydrated using a press. However, even after dehydration, a significant amount of moisture remains (e.g., in the range of 20% to 50% by weight), making it difficult to handle even during extrusion processes.
[0076] It has been found that adding 0.2% to 0.4% wt% cellulose fiber (CFF Topcel) to washed anthracite tailings promotes anthracite extrusion by controlling moisture content. The level of fiber added depends on the moisture content, with higher levels of fiber required for processing samples with high moisture content. Furthermore, flow resistance increases due to the higher shear forces required to process the anthracite-fiber mixture.
[0077] Example 4: Nickel-iron alloy
[0078] A nickel-iron alloy with a particle size ranging from 0.1 mm to 8 mm was combined with 30 wt% polyvinyl alcohol and 0.3 wt% polyacrylonitrile fibers. The high density of the nickel-iron alloy limited the amount of liquid binder that could be added, making it generally difficult to form a satisfactory film for bonding. Furthermore, the mixture became saturated and therefore could not be compacted. The presence of the fibers enabled the briquetting process to be achieved at moisture levels where nickel-iron alloys typically do not bind.
[0079] It should be understood that the method of the present invention can be implemented in various ways, and only a few of them have been shown and described above.
[0080] Example 5: Iron particles
[0081] Agglomerates are produced from blends of byproduct streams with high residual iron content. Agglomerates are formed using a Komarek Dh450 roller press at a pressure of 210 bar.
[0082] To achieve satisfactory green ball strength and final strength, fibers are added to the proprietary binder formulation at a dosage of 0.0% to 0.5%. A 0% fiber test is included as a comparative example.
[0083] Yield is calculated as the weight of the clumps formed when the material first passes through the press.
[0084] Strength was measured by testing individual clumps to peak load at a load rate of 10 mm / min using a Mecmesin Omni-test compressive strength tester. Average results were recorded for 6 clumps per variable. Green ball strength was tested less than 1 hour from the start of production, and cured strength was tested 48 hours after production.
[0085] Results and observations:
[0086]
Claims
1. A cold-formed mass, comprising: (i) Particulate materials; (ii) 0.1% to 0.4% by weight of fibers, wherein the fibers have a length in the range of 1 mm to 5 mm and a diameter in the range of 10 µm to 100 µm; and (iii) An adhesive in the range of 0.2% to 0.8% by weight, wherein the adhesive is selected from: at least partially saponified polyvinyl alcohol, a combination of polyvinyl alcohol and sodium hydroxide, alkali metal alkyl silicates or polyalkyl silicates, phenolic resins, guar gum, a combination of guar gum and calcium oxide, anionic polyacrylamide, styrene acrylate emulsions and combinations thereof.
2. The agglomerate according to claim 1, wherein the fiber is a cellulose-containing fiber.
3. The clump according to claim 1 or claim 2, wherein the fiber is derived from textiles or paper.
4. The agglomerate according to any of the preceding claims, wherein the bulk density of the fibers is in the range of 20 g / l to 500 g / l.
5. The agglomerate according to any of the preceding claims, wherein at least 90% of the fibers have a length of 0.2 mm to 5 mm.
6. The agglomerate according to any of the preceding claims, wherein the particulate material is selected from: metal ore, metal ore-containing waste, iron slag, iron filings, mineral waste, carbon-containing materials, electric arc furnace waste, or combinations thereof.
7. The agglomerate of claim 6, wherein the particulate material is selected from MDF sawdust.
8. The agglomerate according to claim 6, wherein the metal ore comprises iron ore.
9. The agglomerate according to claim 6, wherein the carbonaceous material comprises coke and / or coal.
10. The agglomerate according to any of the preceding claims, wherein the particle size of the particulate material is 4 mm or less.
11. The agglomerate according to any of the preceding claims, wherein at least 10% by weight of the particulate material is capable of passing through a 100 μm sieve before forming agglomerates.
12. The agglomerate according to any of the preceding claims further comprises a crosslinking agent in the range of 0.01% to 5% by weight.
13. The agglomerate according to claim 12, wherein the crosslinking agent comprises glutaraldehyde.
14. The agglomerate according to any of the preceding claims, further comprising a waterproofing agent, said waterproofing agent being bonded to the particulate material or as a layer on the outer surface of the agglomerate.
15. The agglomerate of claim 14, wherein the waterproofing agent comprises a styrene-acrylate copolymer or an asphalt emulsion.
16. The agglomerate according to any of the preceding claims further comprises a carbon additive.
17. The agglomerate according to any of the preceding claims, having a moisture content of <15% by weight.
18. The agglomerate according to any of the preceding claims further comprises a hardening agent.
19. A method for producing lumps according to any of the preceding claims, comprising: (i) Mixing particulate material with fibers ranging from 0.1% to 0.4% by weight, wherein the fibers have a length ranging from 1 mm to 5 mm and a diameter ranging from 10 µm to 100 µm; (ii) Compressing the mixture to form clumps; and (iii) Solidify the mass.
20. The method of claim 19, further comprising the step of mixing one or more of an adhesive, a crosslinking material, and / or a waterproofing agent with the particulate material.
Citation Information
Patent Citations
Sandwich biomass briquette and producing method thereof
CN101148622A
Method for producing iron ore pellet
JP2002212646A